ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KINERJA PEGAWAI DI PUSKESMAS RAROWATU KABUPATEN BOMBANA - Hasma, Hasma; Alim, Andi; Al-Maidin, Achmad R. Muttaqien; Jusuf, Ekafadly (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Employee performance is an important thing to research, because performance is a measure of success in achieving the vision and mission of an agency, in this case the Rarowatu Community Health Center. Good performance will take the agency in a positive direction, and vice versa. This research is a type of quantitative research using the Chi-Square Test and logistic regression test. The results of the research show that the individual characteristic variable with a value of p = <0.001, workload with a value of p = <0.001 and leadership with a value of p = 0.003 has a relationship with employee performance, while the psychological variable with a value of p = 0.158 is not related to employee performance at the community health center. Rarowatu. The existence of a relationship between the independent variable and the dependent variable shows that the worse the individual characteristics, workload and leadership, the worse the results of employee performance. Meanwhile, from the results of the multiple linear regression test, it was found that the independent variables most related to the dependent variable were individual characteristics and leadership. It is recommended that the employees and staff of the Rarowatu Community Health Center hold a briefing at least once a week to evaluate performance each week, add additional staff in the pharmacy section so that queues are not long for pharmacy services, distribute shifts on duty in the morning at the Rarowatu Community Health Center, to the head of the Community Health Center to actively evaluate performance as a leader by involving assessments from employees, for individual characteristics and leadership variables to carry out performance evaluations at least every week.Keywords: Determinants, Implementation, Employee Performance